LifeLab Southampton: a programme to engage adolescents with DOHaD concepts as a tool for increasing health literacy in teenagers –a pilot cluster-randomized control trial. (13th August 2018) - Woods-Townsend, K.; Leat, H.; Bay, J.; Bagust, L.; Davey, H.; Lovelock, D.; Christodoulou, A.; Griffiths, J.; Grace, M.; Godfrey, K.; Hanson, M.; Inskip, H.
Abstract: Adolescence is a critical time point in the lifecourse. LifeLab is an educational intervention engaging adolescents in understanding Developmental Origins of Health and Disease (DOHaD) concepts and the impact of the early life environment on future health, benefitting both their long-term health and that of the next generation. We aimed to assess whether engaging adolescents with DOHaD concepts improves scientific literacy and whether engagement alone improves health behaviours. Six schools were randomized, three to intervention and three to control. Outcome measures were changed in knowledge, and intended and actual behaviour in relation to diet and lifestyle. A total of 333 students completed baseline and follow-up questionnaires. At 12 months, intervention students showed greater understanding of DOHaD concepts. No sustained changes in behaviours were identified. Adolescents' engagement with DOHaD concepts can be improved and maintained over 12 months. Such engagement does not itself translate into behaviour change. The intervention has consequently been revised to include additional components beyond engagement alone.